Repeated administration of phytocannabinoid Δ(9)-THC or synthetic cannabinoids JWH-018 and JWH-073 induces tolerance to hypothermia but not locomotor suppression in mice, and reduces CB1 receptor expression and function in a brain region-specific manner - Tai, S (Pharmacol Res, 2015)
These studies probed the relationship between intrinsic efficacy and tolerance / cross-tolerance between Δ(9)-THC and synthetic cannabinoid drugs of abuse (SCBs) by examining in vivo effects and cellular changes concomitant with their repeated administration in mice. Dose-effect relationships for hypothermic effects were determined in order to confirm that SCBs JWH-018 and JWH-073 are higher efficacy agonists than Δ(9)-THC in mice. Separate groups of mice were treated with saline, sub-maximal hypothermic doses of JWH-018 or JWH-073 (3.0 mg/kg or 10.0 mg/kg, respectively) or a maximally hypothermic dose of 30.0 mg/kg Δ(9)-THC once per day for 5 consecutive days while core temperature and locomotor activity were monitored via biotelemetry. Repeated administration of all drugs resulted in tolerance to hypothermic effects, but not locomotor effects, and this tolerance was still evident 14 days after the last drug administration. Further studies treated mice with 30.0 mg/kg Δ(9)-THC once per day for 4 days, then tested with SCBs on day 5. Mice with a Δ(9)-THC history were cross-tolerant to both SCBs, and this cross-tolerance also persisted 14 days after testing. Select brain regions from chronically treated mice were examined for changes in CB1 receptor expression and function. Expression and function of hypothalamic CB1Rs were reduced in mice receiving chronic drugs, but cortical CB1R expression and function were not altered. Collectively, these data demonstrate that repeated Δ(9)-THC, JWH-018 and JWH-073 can induce long-lasting tolerance to some in vivo effects, which is likely mediated by region-specific downregulation and desensitization of CB1Rs.